Synthesis of Multisubstituted Guanidines through Palladium-Catalyzed Insertion of Isonitriles - Li, Pei-Xia; Meng, Xiu-Jin; Yang, Li; Tang, Hai-Tao; Pan, Ying-Ming (Synlett, 2018)
A new method for the synthesis of multisubstituted guanidines through tandem intermolecular insertion of isonitriles with unactivated amides has been developed. In this study, isonitriles could be used not only as reaction materials but also as the source of amines.
Keywords: insertion of isonitriles; unactivated amides; cascade transformation; palladium